On the Turkish species of Sunius. V. New species, additional records, a new synonymy, and an updated key to species (Coleoptera: Staphylinidae, Paederinae). - Assing, Volker (Contributions to Entomology = Beiträge zur Entomologie, 2005)
Three species of Sunius Curtis, 1829 from southern Turkey are described, illustrated, and distinguished from similar congeners: S. goektepensis sp. n. (Mersin), S. amanensis sp. n. (Antakya), and S. hatayanus sp. n. (Antakya). All of them are micropterous and probably local endemics. Sunius rastrifer Assing, 2001, syn. n. is synonymised with S. dolabrifer Assing, 2001. Additional records are presented for four species. The distributions of seven species are mapped. 17 species of Sunius are now known from Turkey, including one name of doubtful identity. An updated key to the Turkish representatives of the genus is presented. Keywords Coleoptera, Staphylinidae, Paederinae, Sunius, Palaearctic region, Turkey, taxonomy, new species, new records, new synonym, distribution, endemism. Nomenclatural Acts amanensis Assing, 2005 (Sunius), spec. n. goektepensis Assing, 2005 (Sunius), spec. n. hatayanus Assing, 2005 (Sunius), spec. n. rastrifer Assing, 2001 (Sunius), syn. n. of Sunius dolabrifer Assing, 2001